Multivariate Development and Validation of a Stability-Indicating HPLC Method for the Determination of Glimepiride in Tablets - Bonfilio, Rudy [UNESP]; Peres, Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Araujo, Magali B. de; Tarley, Cesar R. T. (Aoac Int, 2013)
This paper describes the multivariate development of a stability-indicating HPLC method for the quantification of glimepiride in pharmaceutical tablets. Full factorial design, Doehlert design, and response-surface methodology were used in conjunction with the desirability function approach. This procedure allowed the adequate separation of glimepiride from all degradant peaks in a short analysis time (about 9 min). This HPLC method uses potassium phosphate buffer (pH 6.5; 27.5 mmol/L)-methanol (34 + 66, v/v) mobile phase at a flow rate of 1.0 mL/min and UV detection at 228 nm. A Waters Symmetry (R) C18 column (250 x 4.6 mm, 5.0 mu m) at controlled room temperature (25 degrees C) was used as the stationary phase. The method was validated according to International Conference on Harmonization guidelines and demonstrated linearity from 2 to 40 mg/L glimepiride, selectivity, precision, accuracy, and robustness. The LOD and LOQ were 0.315 and 1.050 mg/L, respectively. The multivariate strategy adopted in this work can be successfully applied in routine laboratories because of its fast optimization without the additional cost of columns or equipment.